Enhancing photocatalytic activity of tungsten trioxide under visible light irradiation through silver nanoparticle deposition - Low, Harry Kee Kia (2014)
Rhodamine B (RhB) and Methylene blue (MB) are common dyes that are widely used in textile industry remain an environmental challenge. Though many reports on dye related water contaminations were highlighted during international forum, dye pollutant remains a current and rising concern of many researchers. With much attention received on photogradation of dye, hence this FYP will focus on tungsten trioxide (WO3), a highly efficient photocatalytic material, anchored with silver (Ag) nanoparticles to degrade dye. Ag nanoparticles are successfully anchored onto WO3 nanoplate to form synthesized composites (Ag/WO3) via visible light irradiation with various times (0.5hr, 1hr, 2hr). Ag/WO3 composities were characterized by high resolution transmission electron microscope (HRTEM), electrondispersive X ray (EDX), diffuse reflectance ultraviolet-visible spectroscopy (UV-Vis) and X-Ray Diffraction (XRD). The results indicate Ag nanoparticles were effectively anchored onto WO3 surface. The photocatalytic activities of Ag/WO3 were investigated for the degradation of RhB and MB. The Ag/WO3 composite with irradiation time of 0.5hr is found to be more efficient than pure WO3 and Ag/WO3 of 1hr and 2hr. The Ag nanoparticles demonstrated being a significant factor affecting degradation rate and exposure to longer light irradiation time does not show better efficiency.